A Cognitive Semantic Study of the Arabic Preposition “khilāl” (Journal of Misan Researches, 2024)
This study aims to demonstrate the concept of the Arabic preposition "khilāl" from a cognitive semantic perspective. Prototype theory, image schema, and metaphor theory are used to analyze the data Some of the Arabic expressions are chosen to be analyzed. It has been found that the spatial meaning of the preposition "khilāl" is its prototype meaning. The source-path-goal schema and the spatial metaphor are used to extend the meaning of the word from the spatial to non-spatial domains. These results lead to the conclusion that a given preposition's prototype meaning, "khilāl" is the source of all of its non-prototypical meanings.